A high wear-resistant PBT composite material and its preparation method and application

By using the synergistic effect of potassium titanate whiskers, polytetrafluoroethylene resin and silicone masterbatch in PBT composite materials, the problem that existing materials cannot take into account both wear resistance and mechanical properties is solved, and the combination of high wear resistance and good mechanical properties is achieved, and the crystallization rate of the material is improved.

CN117467254BActive Publication Date: 2025-03-25KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311622582.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-03-25
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Existing wear-resistant PBT composite materials cannot take into account both wear resistance and mechanical properties, resulting in severe wear in metal contact parts, affecting the reliability of functional parts.

Method used

By adding potassium titanate whiskers as wear-resistant filler to the PBT composite material, polytetrafluoroethylene resin acts as wear-resistant synergistic agent, and synergistically with the surface improver containing silicone, the component ratio and particle size of the material are optimized to improve the wear resistance and mechanical properties of the material.

Benefits of technology

It is achieved that while maintaining the mechanical properties of PBT materials, it is significantly improved, and the crystallization rate of the materials are improved and the processing performance is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a highly wear-resistant PBT composite material, a preparation method thereof and an application thereof, and relates to the technical field of engineering plastics. The highly wear-resistant PBT composite material of the present invention comprises the following components by weight: 40-50 parts of PBT resin, 25-30 parts of wear-resistant filler, 5-8 parts of wear-resistant synergist, 1-4 parts of surface improver, the wear-resistant filler is potassium titanate whisker, and its average fiber length is 10-20 μm; the wear-resistant synergist is polytetrafluoroethylene, and its particle size Dv50 is 12-15 μm; the surface improver is silicone masterbatch. The present invention adds potassium titanate whisker, polytetrafluoroethylene composite and silicone masterbatch to the PBT material for synergistic effect, obtains a PBT composite material with high wear resistance, and at the same time accelerates the crystallization rate, and has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of engineering plastics, and more specifically to a high wear-resistant PBT composite material and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) engineering plastics have excellent mechanical properties, solvent resistance, electrical properties, heat resistance, gloss, low water absorption and easy processing. The PBT material is modified through various methods such as glass fiber reinforcement, flame retardant and fireproofing to make the modified PBT material have high strength, high toughness, high glow wire, high CTI and other characteristics. It has been widely used in electronic and electrical functional components such as cooling fans, motor housings, relays, connectors, plugs, etc. Some functional components are in contact with metal, and metal parts need to be active for a long time to realize the functions of structural parts such as motor switch control keys. Therefore, it is necessary to have high wear resistance requirements for plastic parts in contact with metal parts. If the wear resistance of the material is not good enough, such as severe wear on the contact surface during the back and forth movement of the metal parts, it is easy to cause the failure of the functional parts. Therefore, it is necessary to improve the wear resistance of the material.

[0003] The prior art discloses a low-warpage wear-resistant conductive PBT composite material, comprising 40-90 parts of PBT resin, 5-20 parts of wear-resistant agent, 5-40 parts of modified whiskers, 0.1-2 parts of nucleating agent, 0.1-1 parts of antioxidant, and 0.1-2 parts of lubricant; the modified whiskers are silicon carbide whiskers, calcium sulfate whiskers, potassium titanate whiskers, and zinc oxide whiskers coated with metallic silver on the surface. Although the low-warpage wear-resistant conductive PBT composite material improves the wear resistance, the mechanical strength is affected, and the wear resistance of the PBT material cannot be improved while maintaining the mechanical strength of the PBT material unchanged. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects and shortcomings of existing wear-resistant PBT composite materials that cannot take into account both wear resistance and mechanical properties, and to provide a high wear-resistant PBT composite material that, through the synergistic effect of various components, improves the wear resistance of the PBT material while also having good mechanical properties and crystallization rate.

[0005] Another object of the present invention is to provide a method for preparing a highly wear-resistant PBT composite material.

[0006] Another object of the present invention is to provide an application of a highly wear-resistant PBT composite material in the preparation of electronic and electrical functional components.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A high wear-resistant PBT composite material comprises the following components in parts by weight.

[0009] PBT resin 40-50 parts, wear-resistant filler 25-30 parts, wear-resistant synergist 5-8 parts, surface improver 1-4 parts, other additives 0-7 parts,

[0010] The wear-resistant filler is potassium titanate whisker, and the fiber length thereof is 10 to 20 μm;

[0011] The wear-resistant synergist is polytetrafluoroethylene, and its particle size Dv50 is 12 to 15 μm;

[0012] The surface improver is silicone masterbatch.

[0013] Among them, it should be noted that:

[0014] In the highly wear-resistant PBT composite material of the present invention, the ratio of the weight of the wear-resistant filler to the total weight of the wear-resistant synergist and the surface improver is preferably (2.5-4.5):1.

[0015] The high wear-resistant PBT composite material of the present invention adopts potassium titanate whiskers as wear-resistant fillers, and cooperates with polytetrafluoroethylene resin as wear-resistant synergists, and compounded with silicone-containing surface improvers. The molecular chains of silicone in silicone masterbatch are relatively smooth and have low surface tension, and are easily migrated to the surfaces of potassium titanate whiskers and polytetrafluoroethylene particles to form films, which plays a role in isolating friction surfaces and reducing friction losses. In the present invention, the size of potassium titanate whiskers and polytetrafluoroethylene resins and the weight ratio of the wear-resistant filler weight to the wear-resistant synergist and surface improver also need to be controlled in a coordinated manner. The length of potassium titanate whisker fibers and the particle size of polytetrafluoroethylene resins will affect their synergistic effect, so that the wear resistance of the material is not significantly improved.

[0016] Specifically, the length of potassium titanate whisker fibers is too short and the particle size of polytetrafluoroethylene is too small, both of which will cause the overall wear-resistant component to easily agglomerate during extrusion. Not only can the potassium titanate whiskers not be fully mixed with polytetrafluoroethylene, but they also cannot be fully mixed with the matrix resin PBT resin. They are prone to peeling off as a whole during friction, increasing friction.

[0017] When the length of potassium titanate whisker fiber is too long and the particle size of polytetrafluoroethylene is too large, on the one hand, it is not conducive to the mixing effect of the two. On the other hand, the content of potassium titanate whisker and polytetrafluoroethylene at the wear contact surface is relatively small, and the wear debris is easily cleared out of the wear surface, which increases the friction and cannot have a good wear-resistant effect. And potassium titanate whisker fiber of a certain length also has a significant reinforcing effect on PBT composite materials, specifically, it can significantly improve the mechanical properties of the material, such as improving tensile strength. If the length of the whisker is too long and the particle size of polytetrafluoroethylene is too large, the contact area between the whisker and polytetrafluoroethylene and PBT resin will decrease, and the mutual force will also decrease, resulting in a decrease in mechanical strength. However, if the length of the whisker is too short and the particle size of polytetrafluoroethylene is too small, it is easy to agglomerate during the extrusion process, making the composite material prone to defects. The defects cause stress concentration, which is first destroyed to form cracks, and then the tensile strength of the composite material is reduced.

[0018] At the same time, in addition to having good friction resistance, the PBT composite material of the present invention has a crystallization rate. Potassium titanate whiskers and polytetrafluoroethylene play a role as nucleating agents, and silicone masterbatch plays a role in strengthening the activity of PBT molecular chains, which helps to improve the crystallization rate. However, if the three are used in too large an amount, the entanglement of different polymer molecular chains affects the crystallization rate, or if one of them is missing, the improvement in crystallization rate is not obvious. The improvement in crystallization rate helps to increase the injection molding speed of the material and shorten the molding cycle.

[0019] Preferably, the anti-wear synergist is polytetrafluoroethylene, and its particle size Dv50 is 13-14 μm.

[0020] Preferably, the following components are included in parts by weight:

[0021] 40-50 parts of PBT resin, 27-29 parts of wear-resistant filler, 6-7 parts of wear-resistant synergist, 2-3 parts of surface improver, and 2-7 parts of other additives.

[0022] In a specific implementation, it is preferred that the silicone masterbatch has a silicone mass content of 50-55%, and the carrier is low-density polyethylene.

[0023] Among them, it should be noted that:

[0024] The composition of the silicone masterbatch of the present invention is as follows:

[0025] Silicone mass content 50-55%

[0026] The mass content of low-density polyethylene is 50-45%.

[0027] In a specific implementation, preferably, the intrinsic viscosity of the PBT resin is 0.8 to 1.3 dl / g.

[0028] Among them, it should be noted that:

[0029] The intrinsic viscosity of PBT resin is tested according to Method A (capillary viscometer method) in GB / T14190-2017.

[0030] The present invention has no special requirements for the intrinsic viscosity of the PBT resin. When the intrinsic viscosity of the PBT resin is 0.8-1.3 dl / g, the dispersion uniformity of the PBT resin, the whiskers and the polytetrafluoroethylene particles during extrusion can be further improved, thereby improving the friction performance. When the intrinsic viscosity of the PBT resin is 0.8-1.3 dl / g, the shear during extrusion can be further controlled by the resin viscosity, and the length of the potassium titanate whiskers and the film formed by the silicone are not easily destroyed, thereby being more conducive to improving the wear resistance.

[0031] Preferably, the intrinsic viscosity of the PBT resin is 0.95 to 1.25 dl / g

[0032] In a specific embodiment, according to actual production needs, the high wear-resistant PBT composite material of the present invention may also be added with other additives, for example, in parts by weight, the other additives include: 2-5 parts of toughening agent, 0.1-0.5 parts of antioxidant and 0.3-0.5 parts of lubricant.

[0033] In a specific embodiment, the toughening agent of the present invention may be a toughening agent conventionally used in the art, for example, it may be one or more of ethylene-methyl acrylate copolymer (EMA) or ethylene-butyl acrylate copolymer (EBA).

[0034] In a specific embodiment, the lubricant of the present invention may be a lubricant commonly used in the art, for example, one or more of aliphatic carboxylic acid ester and polyolefin wax lubricants.

[0035] In a specific embodiment, the antioxidant of the present invention can be an antioxidant conventionally used in the art. Preferably, the antioxidant is a combination of a hindered phenol antioxidant as the main antioxidant and a phosphite antioxidant as the auxiliary antioxidant, wherein the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 2:1 to 1:1.

[0036] The present invention also specifically protects a method for preparing a highly wear-resistant PBT composite material, comprising the following steps:

[0037] After uniformly mixing the components except the wear-resistant filler, the components are mainly fed into the twin-screw extruder. The wear-resistant filler enters the twin-screw extruder through the side feed. The temperatures of the screws of the twin-screw extruder from the feed port to the die are 220°C-230°C, 230°C-240°C, 230°C-240°C, 230°C-240°C, 240°C-250°C, 240°C-250°C, 230°C-240°C, 240°C-250°C, 240°C-250°C, and the screw speed is 400-500rpm. Under the conveying and shearing action of the twin-screw extruder, the PBT composite material particles with high wear resistance are obtained through melt plasticization, kneading and mixing, extrusion, drawing, cooling and pelletizing.

[0038] In a specific embodiment, in the method for preparing the highly wear-resistant PBT composite material of the present invention, the melting temperature and the extruder speed can be adjusted according to actual needs.

[0039] Among them, in the specific preparation method, the PBT resin is pre-dried, and the specific operation is as follows:

[0040] The PBT resin is pre-dried at 120-140°C for 4-6 hours, and the moisture content is controlled to be less than 0.03%. The purpose of controlling the moisture content is mainly to prevent the hydrolysis of the PBT resin during high-temperature extrusion.

[0041] The present invention also specifically protects the use of a high wear-resistant PBT composite material in the preparation of electronic and electrical functional components.

[0042] The high wear-resistant PBT composite material of the present invention has excellent wear resistance and mechanical properties, can meet the wear resistance requirements of plastic parts in long-term active contact with metals, and is widely used in the preparation of electronic and electrical functional components, such as cooling fans, motor switch housings, temperature control switch housings, fuse housings, relays, connectors, plugs, etc.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The present invention adds potassium titanate whiskers and polytetrafluoroethylene into polybutylene terephthalate (PBT) material for compounding, and obtains a PBT composite material with high wear resistance through synergistic effect with a silicone-containing polymer masterbatch. At the same time, the half-peak width of the crystallization is significantly reduced, the crystallization speed is accelerated, and the tensile strength is above 65 MPa. The composite material can be widely used in functional components in the electronic and electrical fields. DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0046] The raw material information of the embodiments and comparative examples are described in detail as follows:

[0047] A: PBT resin,

[0048] A1: GX121 (Yizheng Chemical Fiber), intrinsic viscosity 0.98dl / g;

[0049] A2: GX112 (Yizheng Chemical Fiber), intrinsic viscosity 0.82dl / g;

[0050] A3: GL236 (Yizheng Chemical Fiber), intrinsic viscosity is 1.28dl / g;

[0051] B: Wear-resistant filler potassium titanate whiskers:

[0052] B1: TISMO D (Otsuka Chemical, fiber length 10-20 μm);

[0053] B2: AX-316 (Nantong Aoxin, fiber length 2-8 μm);

[0054] B3: H6K-A7 (Shanghai Dianyang, fiber length 25-50 μm);

[0055] B4: H6K-A1 (Shanghai Dianyang, fiber length 10-20 μm);

[0056] C: Wear-resistant synergist, polytetrafluoroethylene resin:

[0057] C1: polytetrafluoroethylene resin, F5A EX (Solvay, particle size Dv 50 is 12.8 μm);

[0058] C2: polytetrafluoroethylene resin, XPP 511 (Solvay, particle size Dv 50 is 20 μm);

[0059] C3: polytetrafluoroethylene resin, F284 (Solvay, particle size Dv 50 is 9 μm);

[0060] C4: polytetrafluoroethylene resin, PTFE-2013AD (Dongguan Lixin, particle size Dv 50 is 14 μm);

[0061] D: Toughening agent:

[0062] D1: EMA ethylene-methyl acrylate copolymer ELVALOY AC 1125, DuPont;

[0063] D2: EBA ethylene-butyl acrylate copolymer ELVALOY AC 34035, DuPont;

[0064] D3: EVA ethylene-vinyl acetate copolymer ELVAX 265A, Dow;

[0065] E: Surface improver:

[0066] E1: silicone masterbatch, MB50-002 (Dow Corning), the silicone masterbatch has a silicone content of 50% by mass, and the carrier is low-density polyethylene with a mass content of 50%;

[0067] E2: surface improver EAA copolymer wax, AC 540A (Honeywell);

[0068] E3: Silicone masterbatch, GT-600 (Jiahua Fine Chemical), the silicone masterbatch has a silicone content of 60% by mass, and the carrier is low-density polyethylene with a mass content of 40%;

[0069] F: Lubricant:

[0070] Polyolefin wax lubricant, commercially available, was used in all parallel experiments;

[0071] G: Antioxidant:

[0072] 1010 and 168 were mixed in a 1:1 ratio and were commercially available, and the same one was used in all parallel experiments;

[0073] Examples 1 to 10

[0074] A highly wear-resistant PBT composite material comprises the components shown in Table 1 below, in parts by weight.

[0075] Table 1. Examples

[0076] Components 1 2 3 4 5 6 7 8 9 10 A1 45 40 50 45 45 45 45 45 A2 45 A3 45 B1 28 30 25 28 28 28 28 28 28 B4 28 C1 7 8 5 7 7 7 7 7 7 C4 7 D1 3 5 2 3 3 3 3 3 D2 3 D3 3 E1 3 4 1 3 3 3 3 3 3 E3 3 F 0.5 0.4 0.3 0.5 0.5 0.5 0.5 0.5 0.5 0.5 G 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3

[0077] The highly wear-resistant PBT composite materials of the above embodiments 1-10 can be prepared by the following method:

[0078] (1) Prepare various raw materials according to the ratio in Table 1;

[0079] (2) mixing the PBT resin with the wear-resistant synergist, toughening agent, surface improver, antioxidant, and lubricant in a high-speed stirring mixer in proportion to obtain a premix or feeding the premixed mixture separately through a metering feeder into a premixer;

[0080] (3) Feeding the above-mentioned mixed material into a twin-screw extruder, adjusting the feed amount, side feeding in the twin-screw extruder, adding wear-resistant filler in proportion, the temperatures of each section of the screw of the twin-screw extruder from the feed port to the die are 220° C., 230° C., 230° C., 230° C., 240° C., 240° C., 230° C., 240° C., and 240° C., respectively, and the screw speed is 400 rpm. Under the conveying and shearing action of the twin-screw extruder, the mixture is melt-plasticized, kneaded and mixed, extruded, drawn, cooled, pelletized, dried, and packaged to obtain PBT composite material particles with high wear resistance.

[0081] Comparative Examples 1 to 9

[0082] A PBT composite material includes the components shown in Table 2 below, in parts by weight.

[0083] Table 2. Comparative Examples

[0084] Components 1 2 3 4 5 6 7 8 9 A1 45 45 45 45 45 45 45 45 45 B1 28 28 28 35 38 28 B2 28 B3 28 C1 7 7 7 35 10 C2 7 C3 7 D1 3 3 3 3 3 3 3 3 3 E1 3 3 3 3 3 3 E2 3 F 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 G 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3

[0085] The PBT composite materials of Comparative Examples 1-9 can be prepared by the same method as Example 1.

[0086] Results

[0087] The performance of the PBT composite materials prepared in the examples and comparative examples was tested, and the specific testing methods are as follows:

[0088] The product obtained by extrusion and pelletization was dried at 120-130° C. for 3-4 hours, and test specimens were prepared by injection molding according to corresponding standards.

[0089] (1) Tensile strength tested according to ISO 527-1-2012, MPa;

[0090] (2) Wear resistance test was carried out according to method B of JIS K7218-1986; MS-M9000 multifunctional friction tester (Lanzhou Huahui Instrument Technology Co., Ltd.); metal parts were made of S45C steel with a surface roughness Ra between 0.8 and 1 μm; test conditions: load 10 N, linear speed 0.8 m / s, rotation radius 12 mm, test time 64 min, test distance 3 km; the average friction coefficient after 30 min was recorded and the specific wear loss was calculated:

[0091] V S (10 -3 mm 3 / (kg·km)), V S =V / (P×L),

[0092] Where V is the wear amount, V = (W a -W b ) / ρ,Wa is the mass of the test piece before the test, W b is the mass of the test piece after the test, ρ is the density of the test piece, P is the test load, and L is the average sliding distance.

[0093] (3) Crystallization half-peak width test was carried out using a NETZSCH DSC 214 differential scanning calorimeter. 9-12 mg of sample was weighed, the temperature was raised from 30°C to 280°C at a rate of 10°C / min, the sample was kept at 280°C for 3 min, and then the temperature was lowered to 30°C at a rate of 10°C / min. The half-peak width of the crystallization was recorded. The lower the half-peak width of the crystallization, the higher the crystallization rate.

[0094] The specific test results are shown in Table 3.

[0095] Table 3

[0096] Test Results Tensile Strength Friction coefficient Specific wear Crystallization half peak width Example 1 68 0.26 1006 3.8 Example 2 67 0.28 1115 4.4 Example 3 70 0.27 1082 3.7 Example 4 65 0.30 1187 3.9 Example 5 67 0.31 1324 4.2 Example 6 67 0.27 1023 3.7 Example 7 64 0.34 1204 4.3 Example 8 63 0.29 1276 4.1 Example 9 68 0.26 1006 3.7 Example 10 69 0.24 1003 3.9 Comparative Example 1 52 0.52 2085 5.4 Comparative Example 2 55 0.55 2176 5.5 Comparative Example 3 59 0.41 1897 5.3 Comparative Example 4 56 0.42 2012 5.4 Comparative Example 5 57 0.38 1798 5.1 Comparative Example 6 59 0.35 1705 5.7 Comparative Example 7 42 0.53 2105 6.1 Comparative Example 8 58 0.40 1897 6.0 Comparative Example 9 60 0.39 1813 5.8

[0097] As can be seen from the data in Table 3, the friction coefficient of the PBT composite material of the present invention can be reduced to 0.24-0.34, and the specific wear amount is 1006-1324 (10 -3 mm 3 / (kg·km)), has good friction resistance, and the tensile strength can reach 63-70MPa, which improves wear resistance and also has good mechanical properties. It also further increases the crystallization rate and improves the processing performance of PBT composite materials.

[0098] Among them, the PBT resins of Examples 1 and 4 have a more preferred intrinsic viscosity than the PBT resins of Examples 5 and 6, and their friction coefficients can be further optimized and reduced to 0.26, and their specific wear amounts are 1006 to 1054 (10 -3 mm 3 / (kg·km)), has better friction resistance, tensile strength can reach 68-69MPa, and also has better mechanical properties.

[0099] Compared with Example 8, Examples 1 and 7 use more preferred toughening agents, ethylene-methyl acrylate copolymer and ethylene-butyl acrylate copolymer, and their friction coefficients can be further optimized and reduced to 0.26-0.27, and their specific wear amounts are 1006-1023 (10 -3 mm 3 / (kg·km)), has better friction resistance, tensile strength can reach 67-68MPa, and also has better mechanical properties.

[0100] From the comparison between the highly wear-resistant PBT composite material prepared by the present invention and Comparative Examples 1 and 2, it can be seen that when potassium titanate whiskers with a certain fiber length are used as wear-resistant fillers, if the fiber length is too short or too long, the wear resistance and mechanical properties are not significantly improved.

[0101] From the comparison between the highly wear-resistant PBT composite material prepared by the present invention and comparative examples 3 and 4, it can be seen that if polytetrafluoroethylene resin with a certain particle size is used as a wear-resistant synergist, if the particle size is too large, its wear resistance and mechanical properties cannot be significantly improved.

[0102] From the comparison between the PBT composite material with high wear resistance prepared by the present invention and Comparative Example 5, it can be seen that it is also crucial to compound the silicone-containing surface modifier in the present invention. The use of other non-silicone surface modifiers also cannot obtain a PBT composite material with high wear resistance.

[0103] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A highly wear-resistant PBT composite material, characterized in that: In parts by weight, it includes the following components: PBT resin 40-50 parts, wear-resistant filler 25-30 parts, wear-resistant synergist 5-8 parts, surface improver 1-4 parts, other additives 0-7 parts, The wear-resistant filler is potassium titanate whisker, and the fiber length thereof is 10 to 20 μm; The wear-resistant synergist is polytetrafluoroethylene, and its particle size Dv50 is 12 to 15 μm; The surface improver is silicone masterbatch.

2. The highly wear-resistant PBT composite material according to claim 1, characterized in that: In parts by weight, it includes the following components: 40-50 parts of PBT resin, 27-29 parts of wear-resistant filler, 6-7 parts of wear-resistant synergist, 2-3 parts of surface improver, and 2-7 parts of other additives.

3. The highly wear-resistant PBT composite material according to claim 1, characterized in that: The silicone masterbatch has a silicone mass content of 50-55%, and the carrier is low-density polyethylene.

4. The highly wear-resistant PBT composite material according to claim 1, characterized in that: The intrinsic viscosity of PBT resin is 0.8-1.3dl / g.

5. The highly wear-resistant PBT composite material according to claim 1, characterized in that: In parts by weight, the other additives include: 2-5 parts of toughening agent, 0.1-0.5 parts of antioxidant and 0.3-0.5 parts of lubricant.

6. The highly wear-resistant PBT composite material according to claim 5, characterized in that: The toughening agent is one or more of ethylene-methyl acrylate binary copolymer or ethylene-butyl acrylate binary copolymer.

7. The highly wear-resistant PBT composite material according to claim 5, characterized in that: The lubricant is one or more of aliphatic carboxylic acid ester and polyolefin wax lubricant.

8. The highly wear-resistant PBT composite material according to claim 5, characterized in that: The antioxidant is a compound antioxidant of a hindered phenol antioxidant and a phosphite antioxidant.

9. A method for preparing the highly wear-resistant PBT composite material according to any one of claims 1 to 8, characterized in that: The steps include: After uniformly mixing all components except the wear-resistant filler, the main feed is fed into the twin-screw extruder, and the wear-resistant filler enters the twin-screw extruder through the side feed, and melt-plasticization, kneading and mixing, extrusion, drawing, cooling, and pelletizing are performed to obtain PBT composite material particles with high wear resistance.

10. Use of the highly wear-resistant PBT composite material according to any one of claims 1 to 8 in the preparation of electronic and electrical functional components.

Citation Information

Patent Citations

  • Novel wearing-resistant and anti-impact polypropylene composite material and preparation method thereof

    CN109535552A

  • Low-warpage wear-resistant conductive PBT composite material and preparation method thereof

    CN111560158A